II-Indonesian Conference on Clinical Pharmacy - On Clinical Pharmacy", "2nd Indonesian Conference (Asian Journal of Pharmaceutical and Clinical Research, 2016)
II-Indonesian Conference on Clinical Pharmacy Organized by Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran ( http://farmasi.unpad.ac.id ). Supported by Department of Pharmacy, Universitas Udayana and School of Pharmacy, Institut Teknologi Bandung.General information: www.iccp-ofki.com. Keywords-Conference on Clinical Pharmacy